Location-Specific Net Water Uptake and Malignant Cerebral Edema in Acute Anterior Circulation Occlusion Ischemic Stroke - Cheng, XiaoQing; Tian, Bing; Huang, LiJun; Shen, Xi; Liao, AnYu; Zhou, ChangSheng; Liu, Quan Hui; Pang, HuiMin; Tang, JinJing; Luo, BaiYan; Tian, Xia; Hou, YuXi; et al. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: Early identification of malignant cerebral edema (MCE) in patients with acute ischemic stroke is crucial for timely interventions. We aimed to identify regions critically associated with MCE using the ASPECTS to evaluate the association between location-specific net water uptake (NWU) and MCE.MATERIALS AND METHODS: This multicenter, retrospective cohort study included patients with acute ischemic stroke following large anterior circulation occlusion. The ASPECTS was determined by RAPID ASPECTS software. ASPECTS-NWU and Region-NWU were calculated automatically by comparing the Hounsfield unit values in the ischemic and contralateral regions. Critical ASPECTS MCE regions and Region-NWU were evaluated by multivariate logistic regression and the areas under the receiver operating characteristic curves (AUCs).RESULTS: The study included 513 patients. Multivariate analysis showed that the ASPECTS insula (OR = 2.49; 95% CI, 1.44–4.31) and M5 (OR = 1.59; 95% CI, 1.11–3.41) regions were significantly associated with MCE. After adjustment, only the insula (OR = 2.34; 95% CI, 1.23–4.45) was independently associated with MCE. Univariable receiver operating characteristic curve analysis found AUCs for Insula-NWU (AUC, 0.70; 95% CI, 0.65–0.76) and ASPECTS-NWU (AUC, 0.64; 95% CI, 0.58–0.70). The Insula-NWU had better diagnostic power than ASPECTS-NWU (DeLong test; P = .01). A multivariate regression model that combined the NIHSS, ASPECTS, insula involvement, and Insula-NWU had good discriminatory power (AUC = 0.80; 95% CI, 0.74–0.86) and better diagnostic power than Insula-NWU (DeLong test; P < .01).CONCLUSIONS: The insula region is critical for MCE, and Insula-NWU has better prediction efficacy than ASPECTS-NWU. This method does not rely on advanced imaging, facilitating rapid assessment in emergencies.AUCarea under the receiver operating characteristic curveHUHounsfield unitMCEmalignant cerebral edemaNWUnet water uptakeROCreceiver operating characteristic curve